Improving the Skills of the Sanrobone Collection Tailor Business Group through Non-Formal Education in Sanrobone Village, Takalar Regency - Nurmiah Muin; ST Rabiah; Andi Nur Auliyah Asra (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Businesses in the field of sewing clothes are mostly carried out by housewives. This community service activity aims to improve the skills of the Sanrobone Collection sewing business group through non-formal education in the village of Sanrobone, Takalar district. Activity partners have technical and management problems. The method of implementing the activity is training with a participatory method, which involves partners directly and participates as much as possible in the training. The product output produced based on the activity plan is the mukenah or prayer veil. The training is carried out in stages. For the first stage, material is given about some of the errors that occur in making mukenah which cause discomfort when worn and how to overcome them. After that, it was given how to measure, then how to cut the cloth and finally how to sew so that it was neat. Management problems are carried out in the form of organizational assistance. This community service activity has been carried out and the partners enthusiastically participated in this activity